Lack of IgA subclass restriction in antibody response to phosphorylcholine, beta lactoglobulin and tetanus toxoid. - Conley, M E (1984)
Although there is IgG subclass restriction in the antibody responses to most antigens, our data indicate that the human IgA subclasses, IgA, and IgA2, do not demonstrate a similar antigen specific restriction. We did not find evidence for IgA subclass restriction in the antibody responses to phosphorylcholine (PC), beta lactoglobulin or tetanus toxoid. These antigens were chosen to represent carbohydrate-like versus protein antigens and antigens presented through the mucosal route versus the humoral route. For each of these antigens the proportion of antigen specific IgA that was IgA1 and IgA2 was similar to that of total serum IgA. IgA anti-PC, which is thought to be directed against the phosphorylcholine moieties found on certain bacterial polysaccharides, could be found in the serum of all individuals tested and constituted 0.063-0.088% of the total serum IgA. IgA anti-beta lactoglobulin and anti-tetanus toxoid could be measured only in the serum of selected individuals, usually those with known milk protein sensitivity, or those recently immunized with tetanus toxoid. The lack of marked subclass restriction of IgA responses to these antigens stands in contrast to results obtained by others for IgG antibodies, in which carbohydrates and proteins preferentially stimulate antibodies in different IgG subclasses.